Changes in Anterior Segment Morphology of Iris Bombe before and after Laser Peripheral Iridotomy in Patients with Uveitic Secondary Glaucoma - Wakako Ikegawa; Takashi Suzuki; Koji Namiguchi; Shiro Mizoue; Atsushi Shiraishi; Yuichi Ohashi (Journal of Ophthalmology)
Purpose. To quantify changes in anterior segment (AS) parameters after laser peripheral iridotomy (LPI) using AS-optical coherence tomography (OCT) of iris bombe. Method. AS images of eight eyes were captured before and after iris bombe and more than 2 weeks after LPI (post-LPI) using AS-OCT. We compared the following AS parameters: anterior chamber depth (ACD), anterior chamber volume (ACV), iris curvature (IC), iris thickness at 500 μm from the scleral spur (IT-1) in the middle between the iris root and pupillary margin (IT-2) and 500 μm from the pupillary margin (IT-3) to the anterior chamber angle (ACA) (angle opening distance [AOD750]), and trabecular iris space area. Results. Mean IT-1 and IT-3, but not IT-2, were lower after iris bombe (IT-1, P=0.001; IT-2, P=0.081; and IT-3, P=0.001). There were no significant differences between ACD at pre-LPI and before iris bombe (P=0.096). The mean ACV and AOD750 of iris bombe increased at post-LPI (ACV, P<0.01, and AOD750, P<0.05). The mean IT-1, IT-2, and IT-3 increased at post-LPI (all, P≤0.01). IC decreased at post-LPI (P<0.001), and ACD at post-LPI did not change. Conclusions. The iris extends and becomes thinner during iris bombe. LPI during bombe decreases the IC and increases the ACV and ACA.